The Effect of Teaching Techniques (Storytelling and Show-and-Tell) and Students’ Personality on Students’ Speaking Skill - Rizdki Elang Gumelar (Journal of English Education Studies, 2018)
The purpose of this study is to investigate the effect of teaching techniques (Storytelling and Show-And-Tell) and students’ personality on students’ speaking skill at the third grade students of Islamic Senior High School 69 Persis Matraman Jakarta. This research used a quantitative quasi experimental approach using factorial design. In collecting the data this research used speaking test and questionnaire. The hypothesis analysis used two ways anova. Finding of this study showed that there is no significant difference between the students who use teaching technique by using storytelling and those who use show-and-tell on students’ speaking skill. Moreover, there is also no significant difference of introvert and extrovert student on student’s speaking skill. Furthermore, the last finding shows, there is no significant interaction between both teaching techniques and students’ personality on students’ speaking skill.